Upaya Perlindungan Hukum bagi Perempuan dengan Disabilitas Korban Tindak Pidana Kekerasan Seksual - Junindya Fasya, Sofia (Proceedings Series on Social Sciences & Humanities, 2024)
Indonesia has a fairly large population of people with disabilities. This suggests that the likelihood of violations of the rights of persons with disabilities will also be high. This research aims to determine legal protection for women with disabilities who are victims of criminal acts of sexual violence and determine recovery efforts for women with disabilities who are victims of criminal acts of sexual violence. The research method used is normative juridical with statutory, analytical and case approaches. The data source used is secondary data, consisting of primary, secondary and tertiary legal materials collected through literature study. The research results show that legal protection for women with disabilities who are victims of sexual violence is still not optimal. The inhibiting factors are the lack of specific laws and regulations, stigma and discrimination, as well as the lack of accessibility of legal services. Legal protection for women with disabilities who are victims of sexual violence is a shared responsibility. Synergy is needed between the government, law enforcement officials, civil society organizations and the wider community to achieve justice for them.